ANALISIS FINANCIAL DISTRESS DENGAN MENGGUNAKAN MODEL PREDIKSI ALTMAN Z-SCORE, SPRINGATE DAN ZMIJEWSKI (Studi Empiris pada Perusahaan Manufaktur Sektor Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023) - Febriyanti, Ernita; Prabawa, Santosa Tri; Perdana, Dian Noor Citra (JURNAL ILMIAH EDUNOMIKA, 2025)
Global economic uncertainty and tight competition in the consumer goods industry have heightened the risk of financial distress among companies. Early identification is essential to avoid bankruptcy and protect stakeholders’ interests. This study aims to evaluate and compare the accuracy of financial distress prediction using the Altman Z-Score, Springate, and Zmijewski models for manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) during 2021–2023. A descriptive quantitative approach was applied, utilizing secondary data from financial reports published on the official IDX website. The sample consisted of 60 companies selected through purposive sampling from a population of 135. Data analysis included the application of the three models, Kruskal-Wallis and Mann-Whitney tests, as well as calculations of accuracy, Type I error, and Type II error. The findings reveal significant differences in prediction results across the three models. Among them, the Zmijewski model demonstrated the highest accuracy, making it the most reliable for assessing financial distress in this industry.